No beneficial effect of aerobic whole-body electromyostimulation on lower limbs strength and power – a randomized controlled trial - Anne Krause; Christoph Centner; Moritz Walther; Daniel Memmert; Nicolas Walser; Ramona Ritzmann (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background Applying whole-body electromyostimulation (wbEMS) to voluntary activation of the muscle is known to impact motor unit recruitment. Thus, wbEMS as an additional training stimulus enhances force-related capacities. This study aimed to evaluate the mono- and multiarticular strength adaptations to a running intervention with wbEMS compared to running without wbEMS. Methods In a randomized controlled trial (RCT), 59 healthy participants (32 female/ 27 male, 41 ± 7 years) with minor running experience conducted an eight-week running intervention (2x/ week à 20 min) with a wbEMS suit (EG) or without wbEMS (control group, CG). Maximal isokinetic knee extensor and flexor strength and jump height during countermovement jumps were recorded prior and after the intervention to assess maximal strength and power. Results Following eight weeks of running, maximal isokinetic knee extension torque decreased significantly over time for both interventions (EG $$Δ$$ Δ -4%, CG $$Δ$$ Δ -4%; F(1, 44.14) = 5.96, p = 0.02, $${\upeta }$$ η = 0.12). No changes were observed for flexion torque (F(1, 43.20) = 3.93, p = 0.05, $${\upeta }$$ η = 0.08) or jump height (F(1, 43.04) = 0.32, p = 0.57, $${\upeta }$$ η = 0.01). Conclusions The outcomes indicate that there is no additional effect over neuromuscular function adaptations with the inclusion of wbEMS during running training. Knee extensor strength is even slightly reduced which supports the principle of training specificity in regards to strength adaptation. We conclude that strength improvements cannot be achieved by running with wbEMS. Trial registration German Clinical Trials Register, ID DRKS00026827, date 10/26/21.